Criticidade das terras raras para aplicação em veículos elétricos e na energia eólica no Brasil - Paula Junior, Sérgio Eduardo Meirelles de (2017)
Rare earth elements are important components in technologies aimed at decarbonising the economy, such as electric cars and wind turbines. In 2010, China, the world's largest producer of these elements, created difficulties to export them. The dependent countries on Chinese supply have suffered an increase of the prices of more than 600% the following year and were worried about the supply. Thus, several criticality studies were carried out to evaluate whether these elements could be a bottleneck for the consolidation of the fleet expansion plans for electric vehicles and wind energy. Brazil has the second largest reserve of these elements and intends to create a rare earth productive chain with products with high added value. Therefore, the present study has the objective of evaluating if the elements of rare earth could become a bottleneck for the Brazilian plans to expand the fleet of electric vehicles and wind energy.